Emphysematous cholecystitis with perforation and biliary peritonitis (Indian Journal of Case Reports, 2019)
Emphysematous cholecystitis (EC), uncommon but potentially fatal sequelae of acute cholecystitis mainly seen in old-aged patients with high mortality rate, caused by secondary infection of gall bladder with gas-forming enteric organisms. Herein, we report a case of emphysematous gangrenous cholecystitis with perforation and biliary peritonitis in a 76-years-old non-diabetic lady that was successfully managed by surgical intervention coupled with medical. The report of this case highlights the risk of missing this extremely rare but potentially fatal condition once the patient presents in late-stage with concurrent complications like perforation and peritonitis. Therefore, prompt diagnosis and early surgical intervention is imperative are imperative to avoid undesired outcomes.